Continuous wave Laser CO2 efficacy in management of Basel cell carcinoma: clinical study - Khalil, Ali; Ebrahim, Mostafa; Khouri, Eiad (Latakia University Journal -Medical Sciences Series, 2020)
Objective: to study and evaluate esthetic outcomes and cure in the management of Basel cell carcinoma of face skin by using continuous wave Laser CO2. Materials and methods: a total of 12 patients (8 males and 4 females) with mean age 62 years، and diagnosed with basel cell carcinoma on face skin, were treated by traditional scalpel and vaporization of the wound by using CO2 Laser in Tishreen university hospital. The postoperative cosmetic and cure outcomes were recorded after 1 year of surgery. Results: 12 Tumors had been treated: 2(17%) nodular، 7(85%) superfacial and 3(25%) pigmented. The tumors locations: 6 on zygomatic skin, 3 on temporal skin, 1 on forehead skin and 2 on upper lip. Tumors diameters are between 5.5 – 11 with average 7.7. After 1year, the cosmetic results was: 2 tumors ( 16%) bad, 7 tumors (58%) good, 3 tumors (25%) excellent. Tow tumors had been recurred. No statistically significant differences between CO2 laser surgery and cosmetic\recurrence outcomes in accord with Tumor diameter, but it is statistically significant differences in accord with Tumor type. Conclusion: CO2 Laser is effective method in management of Basel cell carcinoma of face skin, because of his good esthetic outcomes without needing of any flaps to close the wounds. هدف البحث: دراسة وتقييم الناحية الجمالية والشفاء اثناء تدبير الورم القاعدي الخلايا لجلد المنطقة الوجهية باستخدام الموجة المستمرة لليزر CO2 المواد والطرق: تتألف العينة من 12 مريض (8 ذكور و 4 اناث) متوسط العمر 62 سنة، تم تشخيص وجود ورم قاعدي الخلايا على جلد الوجه، العلاج باستئصال الورم بالمشرط بهامش أمان 2-3 مم و تبخير الجرح الناتج باستخدام الليزر CO2. تم متابعة الحالة لمدة سنة لمعرفة النتائج التجميلية الحاصلة بعد العلاج، و للتأكد من الشفاء الكامل. النتائج: عدد الأورام 12 ورم توزعت حسب نمط الورم بين 2 (17%) ورم عقدي ، 7 (58%) ورم سطحي، 3 (25%) ورم مصطبغ ، و قد توزعت الآفات كما يلي:6 على جلد الوجنة، 3 على جلد الصدغ ،1 على جلد الجبهة ،2على الشفة العلوية. تراوح حجم الاورام بين 5.5 – 11 مم بمتوسط 7.7 مم. بعد سنة من المراقبة توزعت النتائج من حيث الناحية الجمالية بين2 ورم( 16%) سيئة، 7 ورم (58%) جيدة، 3 أورام ( 25%) ممتازة. تعرض ورمين للنكس (16%) بعد سنة. اعتمادا على حجم الورم لم تشاهد فروق ذات أهمية من الناحية الاحصائية فيما يخص الناحية التجميلية و النكس ، بينما ظهرت الفروق الاحصائية اعتمادا على نوع الورم. الخلاصة: يعتبر الليزر CO2 أداة فعالة في تدبير الورم قاعدي الخلايا على جلد الوجه، لما له من نتائج تجميلية جيدة تعمل على تقليص الحاجة الى تسليخ النسج المجاورة من أجل الحصول على شرائح تغطي الجرح الحاصل.